The psychological health of 207 near-centenarians (95–99) and centenarians from the Sydney Centenarian Study. (October 2019) - Cheng, Adrian; Leung, Yvonne; Crawford, John D; Harrison, Fleur; Sachdev, Perminder; Brodaty, Henry
Objective: While near-centenarians (95–99) and centenarians are the fastest growing sectors of the population in many countries, few studies have investigated their psychological health. We aimed to compare levels of psychological distress and life satisfaction in individuals aged 95 or above (95+) with younger age groups and identify the factors associated with psychological distress and life satisfaction in near-centenarians and centenarians. Methods: We assessed the physical, cognitive, social and psychological health of 207 participants aged 95+ in the Sydney Centenarian Study. Psychological distress and life satisfaction were rated on the Kessler Psychological Distress Scale (K10) and Satisfaction with Life Scale, respectively. Cross-sectional univariate comparisons were performed with participants aged 70–90 years from the Sydney Memory and Ageing Study. Factors associated with psychological distress and life satisfaction among Sydney Centenarian Study participants were examined using multiple regression analyses. Results: In Sydney Centenarian Study and Memory and Ageing Study, mean K10 scores were 15.3 (±5.9) and 13.4 (±3.6), and clinical levels of psychological distress (K10 ⩾ 20) were 19% and 7%, respectively. Sydney Centenarian Study participants demonstrated significantly higher levels and rates of psychological distress ( t = 3.869, p < 0.001; χ 2 = 27.331, p < 0.001). In Sydney Centenarian Study, more psychotropic medications and having fewer relatives and friends were associated with higher psychological distress. Sydney Centenarian Study participants reported significantly higher levels of life satisfaction than Memory and Ageing Study participants, mean scores 6.0 (±1.5) and 5.6 (±1.3); t = 5.835, p < 0.001. Lower Mini-Mental State Examination scores and having fewer relatives and friends were associated with lower life satisfaction in Sydney Centenarian Study. Conclusion: Despite showing higher levels of psychological distress in the prior 4 weeks than younger age groups, near-centenarians and centenarians remained highly satisfied with their overall lives. The identification of risk and protective factors for psychological distress and life satisfaction provides opportunities for interventions to maintain good psychological health in this vulnerable population.